The Risk Factors Predicting Suicidal Ideation Among Perinatal Women in Japan - Kubota, Chika; Inada, Toshiya; Shiino, Tomoko; Ando, Masahiko; Sato, Maya; Nakamura, Yukako; Yamauchi, Aya; Morikawa, Mako; Okada, Takashi; Ohara, Masako; Aleksic, Branko; Murase, Satomi; et al. (Frontiers in Psychiatry, 2020)
Introduction The aim of the present study was to elucidate the foreseeable risk factors for suicidal ideation among Japanese perinatal women. Methods This cohort study was conducted in Nagoya, Japan, from July 2012 to March 2018. The Edinburgh Postnatal Depression Scale (EPDS) questionnaire was conducted at four time points: early pregnancy, late pregnancy, 5 days postpartum, and 1 month postpartum. A total of 430 women completed the questionnaires. A logistic regression analysis was performed using the presence of suicidal ideation on the EPDS as an objective variable. The explanatory variables were age, presence of physical or mental disease, smoking and drinking habits, education, hospital types, EPDS total score in early pregnancy, bonding, and quality and amount of social support, as well as the history of major depressive disorder (MDD). Results The rate of participants who were suspected of having suicidal ideation at any of the four time points was 11.6% (n=52), with the highest (n=25, 5.8%) at late pregnancy. For suicidal ideation, education level (OR: 1.19; 95% CI: 1.00–1.41; p=0.047), EPDS total points in the pregnancy period (OR: 1.25; 95% CI: 1.16–1.34; p<0.000), a history of MDD (OR: 2.16; 95% CI: 1.00–4.79; p=0.049), and presence of mental disease (OR: 2.39; 95% CI: 1.00–5.70; p=0.049) were found to be risk factors for suicidal ideation. Age (odds ratio [OR]: 0.88; 95% confidence interval [CI]: 0.80–0.95; p=.002) and quality of social support (OR: 0.77; 95% CI: 0.60–0.99; p=.041) were found to be protective factors. Conclusion Based on these results, effective preventive interventions, such as increasing the quality of social support and confirming the history of depression, should be carried out in pregnant depressive women at the early stage of the perinatal period.